Mechanisms of ozone-induced neurotoxicity in the development and progression of dementia: a brief review - Marin-Castañeda, Luis A.; Gonzalez-Garibay, Guillermo; Garcia-Quintana, Isabella; Pacheco-Aispuro, Gerónimo; Rubio, Carmen (Frontiers in Aging Neuroscience, 2024)
Dementia encompasses a spectrum of neurodegenerative disorders significantly impacting global health, with environmental factors increasingly recognized as crucial in their etiology. Among these, ozone, has been identified as a potential exacerbator of neurodegenerative processes, particularly in Alzheimer’s disease (AD). Ozone exposure induces the production of reactive oxygen species (ROS), which penetrate the BBB, leading to oxidative damage in neuronal cells. This oxidative stress is closely linked with mitochondrial dysfunction and lipid peroxidation, processes that are foundational to the pathology observed in dementia, such as neuronal death and protein aggregation. Furthermore, ozone triggers chronic neuroinflammation, exacerbating these neurodegenerative processes and perpetuating a cycle of CNS damage. Recent studies highlight the role of peripheral biomarkers like High Mobility Group Box 1 (HMGB1) and Triggering Receptor Expressed on Myeloid cells 2 (TREM2) in mediating ozone’s effects. Disruption of these and other identified proteins by ozone exposure impairs microglial function and response to amyloid plaques, suggesting a novel pathway through which ozone may influence AD pathology via immune dysregulation. This review discusses the concept of a bidirectional lung-brain axis, illustrating that systemic responses to air pollutants like ozone may reflect and contribute to neurodegenerative processes in the CNS. By delineating these mechanisms, we emphasize the critical need for integrating environmental health management into strategies for the prevention and treatment of dementia.